LANGUAGE AND RELIGION: THE USE OF LANGUAGE IN CHRISTIAN LITURGY ON SOME BORDER AREAS OF INDONESIA - Tondo, Fanny Henry (Jurnal Masyarakat dan Budaya, 2018)
In sociolinguistic perspective, the language use could be studied in various domains. One of them is religious domain. The use of language in religious practice, in this case Protestant Christianity in areas where the research location is relatively uniform from one place to another. Bahasa Indonesia (BI) is the dominant language in all liturgy elements. In six areas studied Indonesian hegemony is very strong, not only on state activities and education, but also on religious activities, especially Protestant Christianity. Meanwhile, local languages or local languages fill only a few liturgical elements within a limited scope, ie at 'sermons' and 'chants and choirs'. In some cases, however, the use of local languages can occur during most of these religious occasions, for example in the ceremony of thanksgiving (new gratefulness of the rice). This paper aims to explain the language use in Christianity, especially in some churches in some border areas of Indonesia namely in Alor (East Nusa Tenggara), South Sorong (West Papua), Halmahera (North Maluku), Nunukan-Sebatik (North Kalimantan), Enggano (Bengkulu), and Banda Aceh (Aceh). The data provided is based on the field researches during 2005 – 2014 (for the areas of Alor, South Sorong, Halmahera, dan Nunukan-Sebatik) and it has been enriched by related current secondary data. Meanwhile, on Enggano and Banda Aceh use respectively the data collected in 2015 and 2016. Dalam perspektif sosiolinguistik, pemakaian bahasa dapat dikaji dalam berbagai ranah. Salah satu ranah di antaranya yaitu agama. Pemakaian bahasa dalam praktik keagamaan, dalam hal ini Kristen Protestan di daerah-daerah yang menjadi lokasi penelitian relatif seragam dari satu tempat ke tempat yang lain. Bahasa Indonesia (BI) merupakan bahasa dominan dalam semua elemen liturgy. Pada enam daerah yang diteliti hegemoni bahasa Indonesia sangatlah kuat, tidak hanya pada kegiatan-kegiatan kenegaraan dan pendidikan, tetapi juga pada kegiatan-kegiatan keagamaan, khususnya agama Kristen Protestan. Sementara itu, bahasa daerah atau bahasa lokal hanya mengisi beberapa elemen liturgi saja dalam lingkup terbatas, yakni pada saat ‘khotbah’ dan ‘nyanyian dan koor’. Kendatipun demikian, pada beberapa kasus tertentu pemakaian bahasa lokal dapat terjadi pada hampir sepanjang acara keagamaan tadi, misalnya dalam acara ibadah pengucapan syukur (syukuran padi baru). Tulisan ini bertujuan untuk menjelaskan pemakaian bahasa dalam liturgi Kristen khususnya pada beberapa gereja di wilayah perbatasan Indonesia yakni di Alor (Provinsi Nusa Tenggara Timur), Sorong Selatan (Provinsi Papua Barat), Halmahera (Provinsi Maluku Utara), Nunukan-Sebatik (Provinsi Kalimantan Utara), Enggano (Provinsi Bengkulu) dan Banda Aceh (Provinsi Aceh). Data yang digunakan didasarkan pada penelitian yang dilaksanakan selang tahun 2005 – 2014 (untuk wilayah Alor, Sorong Selatan, Halmahera, dan Nunukan-Sebatik) dan dilengkapi juga dengan data sekunder terkini. Sementara itu wilayah Enggano dan Aceh masing-masing menggunakan data 2015 dan 2016.